Cyberbullying among Children and Youth in Thailand and Measures to Combat It - Sripa, Kantita; Ninphet, Theeravut (Community and Social Development Journal, 2024)
The incidence of cyberbullying among Thai youth has increased recently. Some situations may become severe and challenging to resolve. Consequently, the purpose of this study is to develop regulatory measures that protect young people from cyberbullying, with a focus on integrating collaboration throughout research and development (R&D). Participating in the study were elementary and secondary school students, as well as their families, educators, and experts, in addition to a group of stakeholders from educational institutions, law enforcement departments, and relevant government and civil society organizations. The findings revealed that cyberbullying among children and young people is widespread and takes many different forms. The circumstances related to cyberbullying arise from a youth's lack of understanding of the consequences of bullying, as well as their familial background and social environment. The measures developed to protect youth from cyberbullying included regulatory measures for schools (developing teachers, encouraging students, gaining access to the family, surveillance, and caring) and legal measures (modernizing the law, promoting legal literacy, and protecting youth). Focus should be placed on all levels, including the policy and operational levels. While expanding the study's results, it should be implemented in an approach that integrates with routine duties and operates network-connectedly in order to prevent and solve problems continuously and sustainably.